Arabic Sources for Sicily - Johns, J (British Academy, 2007)
This chapter discusses briefly the history of Sicily from 1025 to 1204. It concentrates mostly on the less-well-known and more complicated periods, specifically the last few years of Islamic Sicily and the passage from Norman rule to the reign of Emperor Frederick II. The politically uncomplicated reign of the Norman kings is mentioned in passing. The chapter also discusses the fate of the Muslims of Sicily under Christian rule, along with the unique mass of Arabic sources from Norman Sicily.